Russia’s economy innovative development in conditions of the import substitution - Bulat N. Kamaev, Azat R. Sadriev, Leysan M. Davletshina, Lyudmila V. Lukishina, (Opción, 2019)
The article aims to investigate Russia’s economy innovative development in conditions of the import substitution. The analysis of the nomenclature of import-substituting products was carried out using the official list of priority and critical types of products, services and software in terms of import substitution and national security. As a result, the model of catching-up development which was being objectively criticized earlier, has once again taken up the leading position in the economic agenda of the state. In conclusion, the sanctions pressure exerted on Russia has affected both the current macroeconomic situation and the system of its promising technological development.